Food safety practices and associated factors among food handlers in food establishments in Adama town, Central Ethiopia - Nimona Gemeda; Tamiru Yazew; Meseret Moroda; Chala G. Kuyu (Frontiers in Sustainable Food Systems)
IntroductionFoodborne infections caused by a variety of variables pose serious public health risks, resulting in significant morbidity and mortality in poor nations like Ethiopia. However, the study contains a deficit in information about food safety practices and associated factors. Thus, this study assessed food safety practices and influencing factors among food handlers in public food establishments in Adama town, Central Ethiopia.MethodsAn institution-based cross-sectional design was used for this study. A total of 319 food handlers were selected through systematic random sampling, with data collected through face-to-face interviews using the Kobo tool. The data were analyzed using descriptive statistics, binary and multivariate logistic regressions using SPSS V-27. Significant factors associated with food safety practices were determined based on Adjusted Odds Ratios (AOR), 95% Confidence Intervals (CI), and a significance level set at p < 0.05.Results and discussionThe findings revealed that 64.79% of food handlers exhibited commendable food safety practices. Factors significantly associated with the food safety practices included knowledge (AOR = 2.106, 95% CI: 1.23–3.606), attitude (AOR = 2.0, 95% CI: 1.169–3.334), ownership status of the establishment (AOR = 2.65, 95% CI: 1.48–4.98), and monthly salary (AOR = 0.516, 95% CI: 0.293–0.906). Food safety practices among food handlers in public food establishments rank as medium compared to other studies conducted in the country. These findings indicates the vital role of education, awareness campaigns, and training programs in promoting safe food handling practices. Therefore, to ensure safe and healthy food, there is a need for targeted interventions, mainly focusing on improving food handler knowledge and attitudes, to enhance food safety standards in public food establishments. It is recommended that authorities and organizations prioritize significant factors identified in this study to reduce foodborne illnesses, ensure public health, and foster a culture of responsible food-handling practices.